2020
DOI: 10.3390/insects11050274
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Shape Variation Patterns in Triatoma infestans (Klug 1834) (Hemiptera: Reduviidae: Triatominae): A First Report in Populations from Bolivia

Abstract: The morphological variations of four populations of geographically isolated Triatoma infestans located in the area of inter-Andean valleys and Chaco of Chuquisaca, Bolivia, were evaluated. Fifty-three females and sixty-one males were collected in the peri-domicile and analyzed with geometric morphometrics tools to study the patterns of the head and wing shape variation. The principal component analysis and canonical variate analysis revealed morphological variations between the populations studied, which were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…This result may be interpreted as a selective process associated with insect body size, since it may be expected that those insects that did not survive to a sublethal dose application were smaller. For T. infestans , larger wings might result from natural selection which favours phenotypes adapted to insecticide exposure [ 52 ]. In previous studies, both female and male T. infestans collected after house spraying with pyrethroid insecticide in a context of moderate resistance had significantly larger wings than their pre-spraying counterparts [ 53 ], and wing size was positively and significantly correlated with total body length [ 54 ], which correlated closely with other metrics of body size (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This result may be interpreted as a selective process associated with insect body size, since it may be expected that those insects that did not survive to a sublethal dose application were smaller. For T. infestans , larger wings might result from natural selection which favours phenotypes adapted to insecticide exposure [ 52 ]. In previous studies, both female and male T. infestans collected after house spraying with pyrethroid insecticide in a context of moderate resistance had significantly larger wings than their pre-spraying counterparts [ 53 ], and wing size was positively and significantly correlated with total body length [ 54 ], which correlated closely with other metrics of body size (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Because of these high temperatures in boreal Chaco (Huacaya/Imbochi) (temperature higher than 30 °C and humidity lower than 20%), the specimens were smaller compared to those from the valley. Vilaseca et al [ 12 ] similarly observed that the centroid size of T. infestans was larger in populations from the inter-Andean valleys compared to specimens from Chaco. In Chaco, variations were observed in T. infestans heads; males had a smaller head and a different shape compared to female heads.…”
Section: Discussionmentioning
confidence: 99%
“…In the last thirty years, studies that analyze the relationship between wild (sylvatic) and domestic T. infestans populations have been performed using linear morphometrics of multiple traits. Recently, geometric morphometrics with the aim to understand patterns of the origins of morphological variation and the level of Chagas infection related to the host and environmental conditions [ 7 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Allometry is defined as the association between size and shape, or the covariation of parts due to a variation in size. It has been highly studied alongside SSD in insects [ 2 , 10 , 28 , 43 , 62 , 63 , 64 , 65 , 66 ] and particularly in beetles [ 24 , 28 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. The type of allometry is classified according to the cause of variation; the inter- and intrasexual shape dimorphism found have a static allometric relationship (for adult insects).…”
Section: Discussionmentioning
confidence: 99%